Evaluación de la calidad del agua mediante el uso de indicadores de calidad en la microcuenca del río Llin Llín, cantón Colta. - Conde Centeno, María Agusta (2024)
This study assesses water quality in the Llin Llín River micro-basin in Colta Canton, Ecuador. The research aims to determine the water quality using various indicators, encompassing physical, chemical, and microbiological parameters. These parameters were evaluated during two distinct climatic seasons: the dry season and the rainy season. Methods such as the National Sanitation Foundation Water Quality Index (NSF), the Oregon Water Quality Index (OWQI), and the index developed by the Regional Autonomous Corporation of Valle del Cauca (ICAUCA) were applied. The results revealed significant variations in water quality between the two seasons, with lower quality during the dry season due to both climatic and anthropogenic influences. The ANOVA statistical analysis highlighted significant differences in water quality values obtained through the different applied indices. This finding underscores the importance of maintaining continuous monitoring and effective management of water resources to preserve and improve water quality in the Llin Llín River micro-basin. Finally, the morphometric configuration of the micro-basin indicates a rapid response to precipitation, thus increasing the risk of erosion and sediment entry. These findings highlight the urgent need to implement soil conservation measures and sustainable basin management practices to mitigate adverse impacts on water quality and promote environmental sustainability in the study area.